Implementasi Model Project Based Learning Berbantuan Media Audio Visual dan Video Editing untuk Meningkatkan Keterampilan Berbicara dalam Pembelajaran Teks Berita pada Siswa Kelas VII B SMP PGRI 1 Denpasar - Sifa, Ananda Aura; Sutama, I Made; Suandi, I Nengah (LP. Ma'arif Janggan Magetan, 2024)
This study aims to describe the implementation, improvement of learning outcomes, and student responses to speaking skills through the application of the Project-Based Learning (PBL) model, supported by audio-visual media and video editing, in the teaching of news texts in Grade VII B at SMP PGRI 1 Denpasar during the 2023/2024 academic year. This classroom action research involved 33 students, with a focus on Indonesian language learning outcomes. Data were collected through observation, learning outcome tests, and student response questionnaires, and then analyzed descriptively, both qualitatively and quantitatively. The findings indicate a significant improvement in students' speaking skills. The average class score in the pre-test was only 54.69%, which increased to 70% in the first cycle with the implementation of the PBL model assisted by audio-visual media. Further improvement was observed in the second cycle, where the average score reached 80.15% with the addition of video editing support, and all students met the criteria for learning objectives achievement. The success of this research was also corroborated by positive student responses to the PBL model.